Pertarungan Makna Atas Pernyataan Cawe-Cawe Presiden Jokowi Mengenai Pemilu 2024 di Media Indonesia - Simamora, Jumadal; Rusadi, Udi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mass media has an important role as a means to reach a wide audience that can influence public opinion in society. Therefore, the media is a social institution that is contested to obtain and win power. Text is a form of ideological practice, language, writing and choice of words that are understood to carry ideological meanings that are used to win public support. In a meeting with the editors-in-chief of mass media and content creators, President Jokowi stated that he would participate in the 2024 elections to ensure that the elections take place safely and smoothly. President Jokowi's statement that he will chat in the 2024 Presidential Election has received pros and cons and has been interpreted differently by the public. The purpose of this study is to find out how the battle for meaning is being carried out by Media Indonesia regarding the statements of President Jokowi's cawe in the 2024 election in the headline news. This study uses a critical paradigm using a political economy media approach. The method used is Halliday's social discourse analysis method which is based on three concepts, namely, the field of discourse, the involvement of discourse and the mode of discourse. Based on the analysis carried out, in its reporting, Media Indonesia chose sources who were dominant against President Jokowi's cawe-cawe statements. Cawe-cawe is interpreted as the President's non-neutrality in the 2024 presidential election, a setback to democracy and as scaring the people. Keywords: Battle of Meaning, Cawe-cawe, 2024 Election, Media Indonesia.